A case of facial nerve palsy in a pediatric patient associated with Covid-19 - Alessandra Iacono; Elisa Pennisi; Consuelo Benincasa; Federico Marchetti (BMC, 2022)
Abstract Background Pediatric facial nerve palsy is acute and mostly idiopathic; other causes are post-infectious forms. Case presentation We describe a rare case of facial nerve palsy associated with COVID-19 in a 5-year-old boy. The diagnosis of post-infectious COVID-19-related facial paralysis was made by serology positivity for a previous infection (IgG positive, IgM and IgA weakly positive), in the presence of a negative molecular nasopharyngeal swab and in the absence of other etiologies. Early treatment with steroids (1 mg/day for 7 days followed by tapering) and supportive care solved the problem. Conclusion In a child with facial paralysis, COVID-19 must be considered as the cause and both nasopharyngeal swab and serology must be performed.